Демографічна характеристика населення села Погреби за даними Генерального опису 1765-1769 рр. - Момот, А. (Краєзнавство, 2016)
У статті, на основі історико-демографічних методик, аналізується населення села Погреби
Яготинської сотні Переяславського полку в другій половині XVIII ст. На основі даних Генерального опису Лівобережної України 1765-1769 рр. визначається чисельність, статево-вікова
та шлюбна структура його мешканців. З'ясовується рівень остаточної безшлюбності та середній вік вступу в перший шлюб. The paper analyses the population of the Pogreby village Yahotyn sotnya Pereyaslav regiment in
the second half of the 18 century. As the main source was used The General description of Left-bank
Ukraine – the census of region, conducted in the years 1765-1769 by order of Empress Catherine II.
Based on census data and using special tools research revealed the total number, sex, age and marriage
structure of the population. Determine the level of final celibacy and the average age of first marriage.
The results are compared with data of another Hetmanschyna’s localities: the Zhuky village Poltava
regiment and towns Pereyaslav and Poltava.
Analysis of the structure of the population of The Pogreby village provides interesting material for
further generalizations and formulating common trends of the rural Hetmanschyna’s society in the
second half of the 18 century. В статье анализируется население села Погребов Яготинской сотни Переяславского полка
во второй половине XVIII века. Основываясь на данных Генеральной описи Левобережной
Украины 1765-1769 гг. определяется численность, половозрастная, брачная структура
социума. Выясняется уровень окончательного безбрачия и средний возраст вступления в
первый брак.